1997
DOI: 10.1002/mats.1997.040060603
|View full text |Cite
|
Sign up to set email alerts
|

Distribution functions and dynamical properties of stiff macromolecules

Abstract: SUMMARYAn analytically tractable model for chain molecules with bending stiffness is presented and the dynamical properties of such chains are investigated. The partition function is derived via the maximum entropy principle taking into account the chain connectivity as well as the bending restrictions in form of constraints. We demonstrate that second moments agree exactly with those known from the Kratky-Porod wormlike chain. Moreover, various distribution functions are calculated. In particular, the static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 70 publications
4
49
1
Order By: Relevance
“…Figure 13(a) suggests that z = 2.43 is quite optimal for a 32-bead chain in the range k ∈ [1.0, 2.4] σ −1 . Corresponding data for the 64-bead chain collapse best for z = 2.54 ± 0.02 in the laboratory frame of reference thus approaching the 8/3 found by Winkler et al 73 We note that the scaling does not break down in Fig. 13(a) for length scales longer than R g such as 2π/(1.0 σ −1 ) ≈ 6.3 nm in the laboratory frame even though R g = 3.92 nm.…”
Section: Dynamical Scalingsupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 13(a) suggests that z = 2.43 is quite optimal for a 32-bead chain in the range k ∈ [1.0, 2.4] σ −1 . Corresponding data for the 64-bead chain collapse best for z = 2.54 ± 0.02 in the laboratory frame of reference thus approaching the 8/3 found by Winkler et al 73 We note that the scaling does not break down in Fig. 13(a) for length scales longer than R g such as 2π/(1.0 σ −1 ) ≈ 6.3 nm in the laboratory frame even though R g = 3.92 nm.…”
Section: Dynamical Scalingsupporting
confidence: 77%
“…The collapse is plotted as a function of (k z t) 2/3 as it has been shown theoretically that log F(x) ∼ x 2/3 for k 3 k B T t/(6πη) 1. 73 Mussawisade et al 64 have confirmed by simulation a theoretic argument 73 stating that the dynamic scaling exponent should, in fact, assume the value of 8/3 similar to a semiflexible polymer in the laboratory frame for k R g 1. Figure 13(a) suggests that z = 2.43 is quite optimal for a 32-bead chain in the range k ∈ [1.0, 2.4] σ −1 .…”
Section: Dynamical Scalingmentioning
confidence: 92%
“…Obviously, the orientation of two successive segments, n, nЈ, is not independent, but connected by the transition probability g(n͉nЈ), 16 which can be obtained from the expression for the elastic energy of the continuum model of the persistent chain 17,18 …”
Section: U͑n I ͒ϭKmentioning
confidence: 99%
“…To extract the scaling relation for the intramolecular dynamics, which corresponds to the prediction (91), we resort to the following considerations. As is well known, the dynamic structure factor for a Gaussian distribution of the differences r i (t)−r j (0) and a linear equation of motion is given by [70,121] S(q, t) = S(q, 0)e…”
Section: Simulation Methods and Modelmentioning
confidence: 99%